(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Hydraulic and pneumatic power systems play a vital role in modern agricultural machinery, directly influencing energy efficiency, operational performance, and environmental sustainability. This review examines recent innovations in hydraulic and pneumatic technologies within the context of Nigerian agriculture, focusing on their potential to enhance productivity while addressing sustainability challenges. The study systematically reviewed literature published between 2013 and 2023 from peer-reviewed journals, technical bulletins, manufacturer reports, and real-world case studies. Key databases searched include ScienceDirect, SpringerLink, Scopus, IEEE Xplore, and Google Scholar. Both simulation-based performance models and real-world field data were analyzed to assess the functional and economic impacts of these systems. A simplified cost-benefit analysis (CBA) framework was applied to evaluate economic feasibility alongside environmental trade-offs. The findings indicate that integrating variable-displacement hydraulic pumps and smart pneumatic control systems can significantly enhance machine precision, reduce energy consumption, and minimize environmental footprints. These systems also support more adaptive and responsive machine operations in diverse agricultural settings, particularly relevant to the climatic and infrastructural conditions in Nigeria. Importantly, this review contributes practical insights to local farming practices and policy formulation by identifying technology adoption pathways that improve farm efficiency while promoting sustainable mechanization. Overall, the study underscores the importance of advancing hydraulic and pneumatic innovations to boost food production efficiency, ensure environmental responsibility, and guide future research, technology deployment, and policy planning in Nigeria and similar regions.